The midcortical-line is more reliable than the T-line in predicting stem anteversion in patients with developmental hip dysplasia after total hip arthroplasty - Jiang, Ziang; Cheng, Rongshan; Kernkamp, Willem Alexander; Xia, Chunjie; Liang, Junjie; Wang, Liao; Tsai, Tsung-Yuan (Frontiers in Surgery, 2022)
Background: Precise preoperative planning improves postoperative outcomes in total hip arthroplasty (THA), especially in developmental dysplasia of the hip (DDH) cases. Previous studies used the T-line and midcortical-line (at different femoral neck levels) as preoperative landmarks to predict postoperative stem anteversion (PSA). However, the most reliable landmark in predicting PSA in DDH patients remains unclear. This study aimed to investigate whether the midcortical-line or T-line is more reliable in predicting PSA, and to find the optimal femoral neck level for predicting PSA in DDH patients. Methods: Pre- and postoperative Computed Tomography (CT) scans of 28 hips in 21 DDH patients who received THA were obtained for three-dimensional femoral models. On the preoperative CT scan, the anteversion of the midcortical-line on the axial cross-sectional plane images (AM-CT), the anteversion of the midcortical-line from 3D models (AM-3D), and the T-line from 3D models (AT-3D) were measured at simulated osteotomy planes at 5 and 10 mm heights proximal to the base of the lesser trochanter. The correlation between the preoperative femoral anteversion (AM-CT, AM-3D, AT-3D) and the PSA was assessed to evaluate the prediction accuracy. Results: The correlations between the AM-CT and the PSA were 0.86 (mean difference (MD) = 1.9o) and 0.92 (MD = -3.0o) at 5 and 10 mm height, respectively. The correlation between the AM-3D and the PSA were 0.72 (MD = -8.0o) and 0.61 (MD = -9.3o) at 5 and 10 mm cutting height. The AT-3D was significantly greater (MD = 19.0o, 11.3o) than the PSA (p-value < 0.01 and p-value = 0.010) at both 5 mm and 10 mm cutting height. Conclusions: The AM-CT at 10 mm height had a strong correlation with the PSA and was more reliable in predicting the PSA when compared with the AM-3D and the AT-3D in DDH patients.